Zero thermal expansion in non-stoichiometric and single-phase (Hf, Nb)Fe2.5 alloy. (May 2023) - Dong, Xuyu; Lin, Kun; Yu, Chengyi; Zhang, Wenbin; Li, Wenjie; Zhang, Qian; Zhang, Qiang; Liu, Jue; Cao, Yili; Xing, Xianran
Abstract: Zero thermal expansion (ZTE) alloys are dimensionally stable under the influence of heat, which is critical in high-precision components but remains rare among single phase materials. This work reports a single phase and nearly isotropic ZTE alloy (Hf0.8 Nb0.2 )Fe2.5 over a wide temperature range of 5–460 K ( αl ≈ 1.07 × 10 −6 K −1 ) via non-stoichiometric regulation. The introduction of excess Fe breaks the dual-phase nature of parent alloy, extends the magnetic ordering temperature, and induces a spin reorientation. The evolution of magnetic structure versus temperature gives rise to the ZTE behavior. The design concept of changing the internal magnetic interaction through non-stoichiometric regulation provides support for the discovery of novel ZTE materials. Graphical abstract: Image, graphical abstract